Comparison of postnatal catch-up growth according to definitions of small for gestational age infants - Jisun Huh; Ji Yoon Kwon; Hye Ryun Kim; Eun Hee Lee; Young-Jun Rhie; Byung Min Choi; Kee-Hyoung Lee (Korean Pediatric Society, 2018)
PurposeSmall for gestational age (SGA) is confusingly defined as birth weight (BW) either below 3rd percentile or 10th percentile for infants. This study aimed to compare postnatal catch-up growth between SGA groups according to different definitions.MethodsData of 129 infants born with BW below the 10th percentile and admitted to Korea University Anam Hospital and Ansan Hospital were retrospectively reviewed. Height and weight were measured at 6, 12, and 24 months. Results were compared between group A (BW: <3rd percentile) and group B (BW: 3rd-10th percentile).ResultsGroup A included 66 infants and group B included 63. At age 6 months (n=122), 62.9% of group A and 71.7% (P=0.303) of group B showed catch-up growth in weight. At 6 months (n=69), 55.9% of group A and 80.0% of group B (P<0.05) showed catch-up growth in height. At 12 months (n=106), 58.5% of group A, and 75.5% (P=0.062) of group B showed catch-up growth in weight. At 12 months (n=75), 52.8% of group A and 64.1% of group B (P=0.320) showed catch-up growth in height. Up to age 24 months, 66.7%/80.0% in group A and 63.6%/80.0% in group B showed catch-up growth in weight/height.ConclusionDespite different definitions, there were no significant differences between the two SGA groups in postnatal catch-up growth up to age 24 months, except for height at 6 months. Compared to infants with appropriate catch-up growth, low gestational age and BW were risk factors for failed catch-up growth at 6 months.